The relationship between physical activity and procrastination behavior among Chinese university students: a chain mediated effect of body self-esteem and overall self-esteem - Zhuan, Sunyoumeng; Cao, Jinjin; Ye, Yongheng; Li, He; Zhang, Qinqin; Wang, Xin (Frontiers in Public Health, 2024)
Objective: This study aimed to explore the relationship between physical activity and procrastination behavior among college students and the serial mediating roles of body self-esteem and overall self-esteem. Methods: A cross-sectional survey was conducted involving 1018 college students. The Physical Activity Rating Scale, the College Students' Physical Self-perception Profile, the Self-Esteem Scale, and the Chinese Procrastination Scale were utilized. Serial mediating effect analysis and Bootstrap analysis were applied to the data. Results: (1) Individuals engaging in high levels of physical activity demonstrated significantly lower levels of procrastination behavior compared to those with moderate or low levels of physical activity (Partial η² = 0.01, F = 2.762, P < 0.01). (2) Physical activity was positively correlated with body self-esteem (r = 0.37, P < 0.01) and overall self-esteem (r = 0.29, P < 0.01), and negatively correlated with procrastination behavior (r = -0.14, P < 0.01). body self-esteem was positively correlated with overall self-esteem (r = 0.11, P < 0.01) and negatively correlated with procrastination behavior (r = -0.13, P < 0.01). Overall self-esteem also showed a significant negative correlation with procrastination behavior (r = -0.26, P < 0.01). (3) Mediation effect analysis indicated that body self-esteem and overall self-esteem played partial mediating roles in the relationship between physical activity and procrastination behavior among college students. The mediating effects were composed of three pathways: "Physical Activity → body self-esteem → Procrastination Behavior," "Physical Activity → Overall Self-Esteem → Procrastination Behavior," and "Physical Activity → body self-esteem → Overall Self-Esteem → Procrastination Behavior," with the effect sizes accounting for 27.70%, 12.26%, and 7.28% of the total effect, respectively.The findings of this study lead to several key conclusions regarding the relationship between physical activity, self-esteem, and procrastination behavior among college students.